Etiology and Outcomes in Elderly Patients Admitted For Acute Infections (Academia Journal of Medicine, 2020)
Background: Infectious diseases are a major cause of mortality in elderly. The present study aimed to assess various acute infections in elderly  population admitting in our department and factors which are associated with their clinical outcomes. Subjects and Methods: Hundred  patients, aged more than 65 years of age, having fever of less than 7 days’ duration or having symptoms of any of the major system admitted in  our department were included. Detailed history, clinical and laboratory work-up was done to diagnose the cause of infection. Mortality of the  patients during hospital stay was noted and factors associated with it were ascertained from statistical analysis. Results: Mean age of the  patients was 75.84 years, two-thirds being males. Hypertension and diabetes mellitus were the most common co morbidities. Pulmonary  infections accounted for majority of the infections (43%), urinary tract infections were the second most common cause of acute infection.  Gastrointestinal infections (10%), central nervous system infections (6%), skin infections (4%) were other less common causes. During  hospitalization, the most common complication was respiratory failure. Overall, 15 patients died during hospital stay. We found higher  APACHE-II score and presence of pulmonary infections to be significantly associated with in-hospital mortality. Conclusion: A multi disciplinary management of elderly patients with infections is required.
Keywords: Aged; Critical Care; ICU; Mortality; Sepsis